2021
DOI: 10.3831/kpi.2021.24.2.54
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerobic Exercise and Acupuncture Treatment on Obese Patients; A Retrospective Case-Controlled Study

Abstract: Objectives The purpose of this study is to investigate the effects of aerobic exercise and acupuncture treatment in obese patients. Methods The effects of exercise in obese patients receiving acupuncture therapy were investigated in this retrospective, case-controlled study in which subjects complying with exercise were enrolled in the case and non-compliers were enrolled in the control group. Results There was a statically significant weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Importantly, these non-pharmacological EATM interventions can be combined with existing behavioral interventions for obesity. For example, a recent retrospective case-controlled study reported a combination of aerobic exercise and acupuncture in obese patients [ 69 ]. However, effective combination methods, patient compliance, and their relative effects with existing behavioral interventions still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these non-pharmacological EATM interventions can be combined with existing behavioral interventions for obesity. For example, a recent retrospective case-controlled study reported a combination of aerobic exercise and acupuncture in obese patients [ 69 ]. However, effective combination methods, patient compliance, and their relative effects with existing behavioral interventions still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%